Test System Design for Determining the Characteristics Properties of Submersible Type Waste Water Pumps - Ali Yavuz Şeflek (Turkish Journal of Agriculture: Food Science and Technology)
In this study; Design and production of a fixed testing platform is made for determining characteristics properties of submersible type waste water pumps that requires between 3 - 22 kW energy. Submersible waste water pumps are used for agricultural plants (for transporting liquid animal fertilizer etc.), drain aging of waste water in bridges and underpasses and other industrial applications. Accurate determination of pump performances in pump manufacturing directly affects the improvement and development of R & D activities For this aim, this study was carried out in a firm which operates in Konya industry and produces different types of pumps. The test stand has been designed and manufactured in 3 different lines as DN 80, DN 125 and DN 150 standard pipe diameters according to TS 12599 standard and centrifugal pump design principles. At the end of the pump tests, the system creates the pump characteristic curves and gives the output data to the user.